Quantification of the Atmospheric Relativistic Electron Precipitation on 17 January 2013. Issue 9 (5th September 2020) - Shekhar, S.; Millan, R. M.; Woodger, L. A.; Qin, M.
Abstract: On 17 January 2013, relativistic electron precipitation (REP) was observed on Balloon Array for Radiation Belt Relativistic Electron Losses (BARREL) payloads, National Oceanic and Atmospheric Administration Polar orbiting Operational Environmental Satellites (NOAA POES), and European Space Agency (ESA) MetOp between 2:44 to 15:04 h UT, scattered across dusk to early morning magnetic local time (MLT) sectors. The observations could be grouped into multiple observations of seven REP events spatially separated by more than 2 h in MLT and at least 1 h in UT. Almost all the events were localized in L shell with dL < 0.5 and MLT with dMLT < 3. A net loss of ∼5% of the relativistic electrons from the radiation belts is estimated between 2:44 to 15:04 h UT (∼13.5 h). A majority of atmospheric REP (nearly 75% through six REP events) was observed before the onset of a minor storm around 14:00 UT; the rest (25% through one REP event) was observed during the commencement of the storm which was followed by a major dropout of MeV electrons from the radiation belts during the main phase. However, no atmospheric precipitation was observed during the main phase, indicating that the dropouts may not have been caused by particle loss into the atmosphere. Key Points: A net atmospheric loss of 5% of the >700‐keV radiation belt particles was obtained between 2:44 to 15:04 UT (∼13.5 h) on 17 January 2013 Nearly 75% of atmospheric loss was prestorm occurring through six REP events (average of ∼12% per REP event) One REP event during the onset of the storm caused ∼25% of atmospheric loss and was followed by flux dropouts during the main phase